Crystallographic Study of the LUMI Intermediate of Squid Rhodopsin - Murakami, Midori (PLoS One, 2015)
Upon absorption of light, the retinal chromophore in rhodopsin isomerizes from the 11-cis to the trans configuration, initiating a photoreaction cycle. The primary photoreaction state, bathorhodopsin (BATHO), relaxes thermally through lumirhodopsin (LUMI) into a photoactive state, metarhodopsin (META), which stimulates the conjugated G-protein. Previous crystallographic studies of squid and bovine rhodopsins have shown that the structural change in the primary photoreaction of squid rhodopsin is considerably different from that observed in bovine rhodopsin. It would be expected that there is a fundamental difference in the subsequent thermal relaxation process between vertebrate and invertebrate rhodopsins. In this work, we performed crystallographic analyses of the LUMI state of squid rhodopsin using the P62 crystal. When the crystal was illuminated at 100 K with blue light, a half fraction of the protein was converted into BATHO. This reaction state relaxed into LUMI when the illuminated crystal was warmed in the dark to 170 K. It was found that, whereas trans retinal is largely twisted in BATHO, it takes on a more planar configuration in LUMI. This relaxation of retinal is accompanied by reorientation of the Schiff base NH bond, the hydrogen-bonding partner of which is switched to Asn185 in LUMI. Unlike bovine rhodopsin, the BATHO-to-LUMI transition in squid rhodopsin was accompanied by no significant change in the position/orientation of the beta-ionone ring of retinal.